Developing Human Capital in Rural Areas: the Indian Experience - Malhotra, Rashpal (2007)
Reproduced below is the speech delivered by Dr Rashpal Malhotra, Director General, Centre for Research in Rural and Industrial Development; at the OECD Annual Conference on ‘Innovative Rural Regions: The Role of Human Capital and Technology’ held at Cacers, Extremandura, Spain on 21-23 March 2007. It focuses on two contemporary issues with reference to rural India: the strengthening of the Panchayati Raj Institutions (PRIs), and setting up of Special Economic Zones (SEZs) involving acquisition of large tracts of land in rural areas.